Review: Waveform Design for Improve Perform Analysis of 5G - Ali, Mohammed Hussien; Sherif, Noora H. (European Journal of Applied Sciences, 2022)
We need to access very large bandwidths in order to accomplish the goal of ubiquitous mobile broadband, where radio access performance should not be a limitation for customer experience. As a result, higher frequency bands up to the millimetre wave region should be taken into consideration. In terms of mobility, energy efficiency, and cost efficiency, the design of the air interface, which involves waveforms, is a crucial element. Four candidate multicarrier waveforms are evaluated by comparing in this study based on a variety of parameter bit error rates (BER), which include orthogonal frequency division multiplexing, filtered orthogonal frequency division multiplexing, universal filtered multicarrier, and generalized frequency division multiplexing to decide which of them is a better option for 5G mobile. The waveforms significantly enhanced spectrum localization and produced suitable spectrum fragmentation, based on the results of the MATLAB simulation. These waveforms successfully solve the problem of time-frequency synchronization by being able to merge different traffic parameters. As a result, these waveforms have a significant amount of promise for orthogonally and synchronization and can manage multiple users without signal degradation. Additionally, they handle all multiple-input and multiple-output applications and scenarios. The simulation's results show the range of these waveforms and propose the optimal ones for use in 5G systems.